Polyols can alleviate chilling injury in ‘Palmer’ mangoes during cold storage - Sanches, Alex Guimarães [UNESP]; Pedrosa, Vanessa Maria Dantas [UNESP]; Checchio, Mirela Vantini [UNESP]; Fernandes, Thiago Feliph Silva [UNESP]; Mayorquin Guevara, Juan Esteban [UNESP]; Gratão, Priscila Lupino [UNESP]; Teixeira, Gustavo Henrique de Almeida [UNESP] (Elsevier, 2021)
Considering the susceptibility of mangoes to chilling injury (CI) during storage at low temperatures (<13 °C), the objective of this study was to evaluate the use of polyols to alleviate the damage caused by CI, and to verify the effect of these additives on the quality and oxidative metabolism of ‘Palmer’ mangoes stored at 8.0 °C for 28 days with subsequent transfer to ambient conditions (23 °C). Therefore, physiologically mature ‘Palmer’ mangoes were harvested and immersed in solutions containing propylene glycol, sorbitol, and glycerol (concentrations, 0.1%, 0.5%, and 2.5%, respectively for 1 h). The fruits were stored at 8 ± 1.0 °C for 28 days and transferred to ambient temperature (23 ± 2.0 °C) every 7 days to evaluate the development of CI, modification of physicochemical parameters, and oxidative metabolism. The symptoms of CI were minimized during cold storage, mainly when the mangoes were treated with sorbitol solutions. Fruits treated with polyols were firmer and showed less fresh weight loss and browning (luminosity), higher titratable acidity, and soluble solids content than the controls. The epicarp (peel) and mesocarp (pulp) of fruits treated with 2.5% sorbitol exhibited lower accumulation of H2O2 and polyphenol oxidase (PPO) activity, higher membrane integrity (malondialdehyde – MDA), and higher activities of superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX); further, sorbitol treatment preserved the ascorbate content in these tissues compared to other treatments. Thus, immersion of mangoes in sorbitol can serve as an alternate strategy to alleviate CI during cold storage.
Keywords: Glycerol; Mangifera indica L.; Oxidative metabolism; Propylene glycol; Sorbitol